Metabolic effects and cardiovascular disease risks of TDF or TAF in patients with chronic hepatitis B: a systematic review and meta-analysis - Zhou, Yuan-Hai; Cai, Nan; Chen, Yu-Xin; Su, Yong-Lu; Hu, Peng (Frontiers in Pharmacology, 2025)
Background and aimsThe effects of Tenofovir Disoproxil Fumarate (TDF) or Tenofovir Alafenamide (TAF) on lipid profiles have been observed in chronic hepatitis B (CHB) treatment. However, the metabolic features and their impact on cardiovascular risk remain unclear. We conducted a systematic review and meta-analysis to evaluate these effects.MethodsWe searched for studies from four major databases (PubMed, Web of Science, EMBASE, and the Cochrane Library) that reported the effects of TDF or TAF on metabolism and cardiovascular disease risk. The changes in metabolic parameters and 10-year atherosclerotic cardiovascular disease (ASCVD) risk were compared with baseline in the TDF and TAF treatment groups. Extracted data were analyzed with the random-effects model or the fixed-effects model. Potential sources of heterogeneity were investigated using sensitivity and subgroup analyses.ResultsA total of 19 studies including 19,396 CHB patients (12,067 in TDF‐only group, 5,423 in TAF‐only group, and 1906 in TDF-switched group) were included in this meta-analysis. We found that both TAF and TDF treatment mildly increase the 10-year ASCVD risk. The TAF treatment showed significant increases in body weight, with no significant effects were observed on lipid levels or blood glucose. While TDF treatment has a lipid-lowering effect and caused weight loss. Subanalyses emphasized the impact of changing antiviral treatment strategies on metabolism. We found an increased risk of dyslipidemia and body weight gain after switching from TDF to TAF treatment.ConclusionAlthough TAF and TDF treatments exhibit different metabolic characteristics, both mildly increase the risk of cardiovascular disease.Clinical Trial Registrationidentifier CRD42024595452